Creep and water loss characteristics in hardening bodies of water-rich filling materials - LIU Juan-hong; ZHOU Qian; ZHAO Xiang-hui (工程科学学报)
In order to investigate the characteristics of deformation and water loss of hardened paste of water-rich filling material under aging effect,the creep property of water-rich filling materials with a certain mass ratio of water to solid was studied in different stress conditions. The deformation characteristics,water loss and its relationship with external load on the filling body in the process of creep were analyzed by using scanning electron microscopy and differential thermal analysis-thermal gravimetry(DTA-TG). It is found that the instability and failure critical stress of water-rich filling materials with a 2.0 water-to-solid mass ratio is 1.96 MPa,which is 90% of their compressive strength. Creep cannot affect the content of combined water in water-rich filling materials. But unbound water in water-rich filling materials can run off when instability and failure happen. The relative loss value of unbound water content is of linear positive correlation with the external load level. The loss of unbound water can induce more interspaces in waterrich filling materials. These cracks are quickly pressed and the hardening body produces large deformation under the external load,which leads to the local instability of the filling body and thus affects the overall stability of the goaf.